Mortality of mothers with opioid-use during pregnancy: an international comparison using linked mother-baby records for England and Ontario. (2018) - Guttmann, Astrid; Blackburn, Ruth; Amartey, Abigail; Zhou, Limei; Wijlaars, Linda; Saunders, Natasha; Harron, Katie; Gilbert, Ruth
No abstract available